(untitled) (Fiep Bulletin - online, 2011)
This paper aims to show the importance of step classes, citing his record since the benefits generated by the frequent practice. It also shows the effects and changes that cause the body and the body, and very clearly how to act so that the lessons become ideal. This study concluded that the step achieves results proved satisfactory in the body, it also offers moments of relaxation and joy to the students, providing the best results also in life in relation to physical, psychological and social.